أثر استخدام برنامج تعليمي قائم على الذكاءات المتعددة - أم الجيلالي, حاكم; بكري, عبد الحميد (My University, 2018)
تهدف الدراسة الحالية إلى معرفة أثر استخدام برنامج تعليمي قائم على الذكاءات المتعددة في معالجة صعوبات تعلم الرياضيات لدى تلاميذ الثالثة ابتدائي ، تكونت العينة من مجموعتين تجريبية و ضابطة و تكونت كل مجموعة من (30) تلميذا تراوحت أعمارهم ما بين (8-10 سنوات).استخدمت الدراسة مقياس الذكاءات المتعددة ، برنامج تعليمي قائم على الذكاءات المتعددة و اختبار تحصيلي بعدي من إعداد الباحثة ، و توصلت النتائج إلى فاعلية البرنامج التعليمي في معالجة صعوبات تعلم الرياضيات لدى تلاميذ الثالثة ابتدائي. The present study aims at finding out the impact of the using a multi-intelligences based learning program in addressing the difficulties of learning mathematics among the third primary students, The sample consisted of two experimental and control groups, A total of 60 students aged between (8-10) years participated in the study distributed into two groups: (30) students in the experimental group and (30)in the control group; he study used the Multiple Intelligences Scale, a multi-intelligency based learning program and a post-secondary achievement test. The results found the effectiveness of the educational program in addressing the difficulties of learning mathematics in third elementary students
في معالجة صعوبات تعلم الرياضيات لدى تلاميذ الثالثة ابتدائي
مقال
Keywords: صعوبات تعلم الرياضيات , البرنامج التعليمي القائم على الذكاءات المتعددة , التعليم الابتدائي, الاختبار البعدي; Educational program based on multiple intelligences; learning difficulties in mathematic